Efektivitas Mesin Slitter Dengan Menggunakan Metode OEE di Perusahaan Packaging - Pahila, Desy Ayu; Maksum, Hapid Apid; Rinaldi, Dimas Nurwinata (Fakultas Teknik Universitas Tulang Bawang, 2024)
XYZ is a company engaged in manufacturing produce packaging products that use machines in the production process. The Slitter machine is one of the main machines in this company's production flow, however, according to research results, downtime often occurs causing the production flow to stop so that losses can occur for the company due to not achieving targets. This research aims to determine the level of effectiveness of the slitter machine at PT. The research method used is an analysis of Overall Equipment Effectiveness calculations and identification of the main causes of low machine effectiveness by applying OEE and Six Big Losses analysis. The results of this research show an OEE value of 81.61% which has not yet reached the ideal World Class condition of 85% and is the biggest factor in the value of losses in Performance Efficiency is 14.606%. Keywords: Downtime, Overall Equipment Effectiveness, Packaging, Six Big Losses.